UJI AKTIVITAS ANTIBAKTERI EKSTRAK METANOL DAUN GAHARU (Aquilaria malaccensis Lamk.) TERHADAP BAKTERI Streptococcus sobrinus dan Salmonella typhi - Kusumawardani, Niken; Saleh, Chairul; Astuti, Winni (Jurusan Kimia FMIPA UNMUL, 2022)
Plants at this time are widely used as medicine because according to some research medicinal materials, plants that have the potential as medicine do not cause too many side effects. One of the plants that are used as medicine is agarwood leaves because it is known to have several medicinal properties, one of them is as an antibacterial drug. This study was conducted to find out the secondary metabolite compounds contained in agarwood leaves and to determine the MIC value of agarwood leaves methanol extract against Streptococcus sobrinus KCCM 11898 and Salmonella typhi ATCC 422, by means of agarwood leaves extracted using methanol, phytochemical screening, and antibacterial activity tests using disc diffusion method. Phytochemical screening of agarwood leaves methanol extract results revealed alkaloids, steroids and phenolics. The MIC value of agarwood leaves methanol extract toward Streptococcus sobrinus KCCM 11898 and Salmonella typhi ATCC 422 is 1.25%.